2004
DOI: 10.1021/ef040013o
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmosphere on Viscosity of Selected Bituminous and Low-Rank Coal Ash Slags

Abstract: The viscosities of nine coal ash slags were measured in air as a function of temperature. Selected slags were also tested in reducing atmosphere and in air with 10% water vapor. In air, the viscosities of the slags can be related to the mole ratio of basic to acidic oxides. An improved fit is obtained from the ratio of oxide ions contributing to the bases to the oxide contributing to the acids. The change in viscosity observed in using hydrogen instead of air appears to be related to the amount of iron origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The oxygen partial pressure inside a coal gasifier is typically on the order of 10 −8 to 10 −9 atm (1 to 0.1 mPa), sufficient to reduce most of the iron present in slags to a Fe 2+ state. A decrease in slag viscosity was observed by Folkedahl and Schobert in their study on the effect of reducing atmospheres on the viscosity of coal ash slags [30]. The effect of oxygen partial pressure on coal ash slag viscosity highlights the importance of matching experimental parameters to gasifier operating conditions in data collection.…”
Section: Viscosity Of Fully Molten Silicatesmentioning
confidence: 82%
“…The oxygen partial pressure inside a coal gasifier is typically on the order of 10 −8 to 10 −9 atm (1 to 0.1 mPa), sufficient to reduce most of the iron present in slags to a Fe 2+ state. A decrease in slag viscosity was observed by Folkedahl and Schobert in their study on the effect of reducing atmospheres on the viscosity of coal ash slags [30]. The effect of oxygen partial pressure on coal ash slag viscosity highlights the importance of matching experimental parameters to gasifier operating conditions in data collection.…”
Section: Viscosity Of Fully Molten Silicatesmentioning
confidence: 82%
“…Slag viscosities greatly impact the rate and ease with which they can be tapped out of the gasifier. A viscosity in the range of 5-25 Pa-s is considered ideal for the operation of slagging gasifiers [3,4]. Higher viscosities result in solidification of the slag before tapping, thus clogging the tapping valves.…”
Section: Introductionmentioning
confidence: 99%
“…Nowok et al [16,17] investigated the effects of atmosphere and local structure of a lignitic coal slag on viscosity. Schobert et al [18,19] reported the fluidity of slag under different atmospheres and flow properties of laboratory ash in a reducing atmosphere. However, little work has been investigated on the rheology of slag, except the studies reported by Tomukayakul et al [20] and Song et al [21].…”
Section: Introductionmentioning
confidence: 99%